Answer
To sketch the graphs:
**a) \( y = 2^{x+1} + 2 \):**
- Shift the basic \( y = 2^x \) graph 1 unit left and 2 units up.
- As \( x \) increases, the graph rises exponentially.
- As \( x \) decreases, it approaches the horizontal asymptote \( y = 2 \).
**b) \( f(x) = -2^{x+1} - 2 \):**
- Reflect the basic \( y = 2^x \) graph over the x-axis and shift it 1 unit left and 2 units down.
- As \( x \) increases, the graph decreases exponentially.
- As \( x \) decreases, it approaches the horizontal asymptote \( y = -2 \).
Plot key points and draw the curves accordingly.
Solution
Sure, let's analyze and describe how to sketch the graphs for both functions:
### Exercise 5: Sketch the Graph
#### a) \( y = 2^{x+1} + 2 \)
**1. Basic Function:**
- Start with the basic exponential function \( y = 2^x \).
**2. Horizontal Shift:**
- The term \( x + 1 \) inside the exponent indicates a **horizontal shift**.
- Specifically, \( y = 2^{x+1} \) shifts the graph **1 unit to the left**.
**3. Vertical Shift:**
- Adding 2 shifts the entire graph **2 units upward**.
- So, \( y = 2^{x+1} + 2 \) moves the graph of \( y = 2^x \) left by 1 and up by 2.
**4. Asymptote:**
- The horizontal asymptote for \( y = 2^{x+1} + 2 \) is \( y = 2 \).
**5. Key Points:**
- Choose some x-values to plot:
- When \( x = -1 \):
\[ y = 2^{-1+1} + 2 = 2^0 + 2 = 1 + 2 = 3 \]
Point: (-1, 3)
- When \( x = 0 \):
\[ y = 2^{0+1} + 2 = 2^1 + 2 = 2 + 2 = 4 \]
Point: (0, 4)
- When \( x = 1 \):
\[ y = 2^{1+1} + 2 = 2^2 + 2 = 4 + 2 = 6 \]
Point: (1, 6)
**6. Sketch Summary:**
- **Start**: The graph approaches the asymptote \( y = 2 \) as \( x \) approaches negative infinity.
- **Increasing**: As \( x \) increases, the graph rises exponentially.
- **Key Points**: Plot the points calculated above and draw a smooth curve passing through them, getting closer to \( y = 2 \) on the left and rising steeply to the right.
---
#### b) \( f(x) = -2^{x+1} - 2 \)
**1. Basic Function:**
- Start with the basic exponential function \( y = 2^x \).
**2. Horizontal Shift:**
- Similar to part (a), \( x + 1 \) inside the exponent indicates a **horizontal shift** of **1 unit to the left**.
- So, \( y = 2^{x+1} \).
**3. Reflection over the x-axis:**
- The negative sign in front of \( 2^{x+1} \) reflects the graph over the **x-axis**.
- Thus, \( y = -2^{x+1} \) flips the graph vertically.
**4. Vertical Shift:**
- Subtracting 2 shifts the entire graph **2 units downward**.
- Therefore, \( f(x) = -2^{x+1} - 2 \) moves the reflected graph left by 1 and down by 2.
**5. Asymptote:**
- The horizontal asymptote for \( f(x) = -2^{x+1} - 2 \) is \( y = -2 \).
**6. Key Points:**
- Choose some x-values to plot:
- When \( x = -1 \):
\[ f(-1) = -2^{-1+1} - 2 = -2^0 - 2 = -1 - 2 = -3 \]
Point: (-1, -3)
- When \( x = 0 \):
\[ f(0) = -2^{0+1} - 2 = -2^1 - 2 = -2 - 2 = -4 \]
Point: (0, -4)
- When \( x = 1 \):
\[ f(1) = -2^{1+1} - 2 = -2^2 - 2 = -4 - 2 = -6 \]
Point: (1, -6)
**7. Sketch Summary:**
- **Start**: The graph approaches the asymptote \( y = -2 \) as \( x \) approaches negative infinity.
- **Decreasing**: As \( x \) increases, the graph decreases exponentially.
- **Key Points**: Plot the points calculated above and draw a smooth curve passing through them, getting closer to \( y = -2 \) on the left and descending steeply to the right.
---
### Visual Comparison:
- **Function (a)** is an exponential growth curve shifted left by 1 and up by 2, with an asymptote at \( y = 2 \).
- **Function (b)** is a reflected exponential decay curve (due to the negative sign) shifted left by 1 and down by 2, with an asymptote at \( y = -2 \).
By plotting the key points and considering the shifts and reflections, you can accurately sketch both graphs.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution